2017
DOI: 10.2147/copd.s117866
|View full text |Cite
|
Sign up to set email alerts
|

Serum cytokine levels related to exposure to volatile organic compounds and PM<sub>2.5</sub> in dwellings and workplaces in French farmers &ndash;&nbsp;a mechanism to explain nonsmoking COPD

Abstract: Although French farmers smoke less on average than individuals from the general population, they suffer more from COPD. Exposure to biological and chemical air pollutants in the farm may be the cause of these higher COPD rates. This study investigates the role of bio-contaminants, including the relationship of exposure to volatile organic compounds (VOCs) and fine particulate matter (of diameter of 2.5 µm [PM2.5]) objectively measured in the farm settings (dwellings and workplaces) to serum cytokines involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 42 publications
0
33
0
Order By: Relevance
“… 17 In addition, an epidemiological study showed that chronic exposure to high levels of VOCs was significantly associated with reduced serum IL-13 concentrations. 18 …”
Section: Discussionmentioning
confidence: 99%
“… 17 In addition, an epidemiological study showed that chronic exposure to high levels of VOCs was significantly associated with reduced serum IL-13 concentrations. 18 …”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which VOCs may act on respiratory health are based on irritation [25] or on the alteration of cytokine levels that may be involved in the inception of respiratory diseases, such as COPD in farmers due to their exposure to these chemicals [26].…”
Section: Discussionmentioning
confidence: 99%
“…In the adult population, exposure to aromatic compounds has been found to be significantly associated with physician-diagnosed asthma (adjusted OR = 1.63, 95% CI: 1.17–2.27) [9]. In addition, total VOCs has been found associated with an increasing risk of shortness of breath in adults [26] and asthma in children [16].…”
Section: Discussionmentioning
confidence: 99%
“…Particulate matter (PM), as an important indicator of air pollution, has aroused widespread concern. As reported, it has correlated with many respiratory diseases [1][2][3]. The animal farmers, they are at a higher prevalence of chronic bronchitis and chronic obstructive pulmonary disease (COPD) than the no-farming people [4][5][6].…”
Section: Introductionmentioning
confidence: 95%